A Laboratory Scale Synthesis of Geopolymer from Locally Available Coal Fly Ash from Brick Industry - Bhandari, Rishi Babu; Pathak, Arvind; Jha, Vinay Kumar (Journal of Nepal Chemical Society, 2013)
In this work, geopolymers have been synthesized from coal fly ash (CFA) using KOH and Na2SiO3 as activators. Some parameters such as alkali concentration, amount of Na2SiO3 and curing time have been varied in order to improve the quality of geopolymeric product. The geopolymerization process was carried out using 3-8 M KOH solutions, Na2SiO3 to CFA mass ratio of 0.25-2.00 and curing time variation from 6-28 days. The curing temperature was fixed at 40°C in all the cases. During the variation of KOH concentration, the maximum compressive strength of 6.62 MPa was obtained with CFA treated with 7 M KOH solution. Similarly, with the variation of the mass ratio of Na2SiO3 to CFA, the maximum compressive strength of 28.1 MPa was obtained with Na2SiO3 to CFA mass ratio of 1.75. Furthermore, the compressive strength was found to be increased with increasing curing time and 41.9 MPa was achieved with 28 days of curing time. DOI: http://dx.doi.org/10.3126/jncs.v29i0.9232 Journal of Nepal Chemical Society Vol. 29, 2012 Page: 18-23 Uploaded date : 12/3/2013